Decoding the Challenges: A Study of English Writing Errors Among EFL Students - Adi Isma; La Ode Rasmin; Samsudin Samsudin (PT. Global Research Collaboration, 2023)
This study focused on analyzing the common errors made by students in their English writing skills. The study employed a descriptive research design, involving 100 EFL university students as participants. The primary data collection method was a writing test, and the collected data were analyzed using error analysis techniques. The findings showed that the most common errors made by the students were related to grammar, vocabulary, and spelling. The most common grammatical errors were associated with subject-verb agreement, verb tense, and articles. In terms of vocabulary errors, the study identified prevalent mistakes such as the incorrect use of word forms, inappropriate collocations, and confusion between homophones. Additionally, the analysis of spelling errors revealed that phonetic spelling mistakes were the most common, followed by misspelling of homophones and confusion of vowels. These findings highlight areas where students commonly struggle with their English writing skills and emphasize the crucial need for targeted instructional strategies to effectively address these challenges and improve students' proficiency in English writing.